Analytical bound for the CCDF of Crest Factor in NC-OFDM Systems - Mohammed Y. Bendimerad; Fatima Debbat; Fethi T. Bendimerad (Journal of Communications Software and Systems, 2015)
Non-contiguous orthogonal frequency division multiplexing (NC-OFDM) is a promising framework for wireless communication systems due to OFDM characteristics like the spectral bandwidth efficiency, robustness to frequency selective fading channels, etc. However, it has been widely known that multicarrier signals generated by OFDM technique exhibit a large peak to average power ration (PAPR), one of the main impediment that has limited the applicability of OFDM systems. Several approaches are employed in literature to derive the PAPR distribution and thus try to reduce it in OFDM context, as Central limit theorem and modern extreme value theory. In new contexts like NC-OFDM systems when flexible access to spectrum is done with non-contiguous portions, the PAPR distribution remains generally unknown, and it is necessary to describe it, since this is one of the key design parameters. In this correspondence, we develop the PAPR bound expression in NC-OFDM context.